The weak instrument problem of the system GMM estimator in dynamic panel data models - Maurice Bun; Frank Windmeijer (Centre for Microdata Methods and Practice (cemmap), 2007)
The system GMM estimator for dynamic panel data models combines moment conditions for the model in first differences with moment conditions for the model in levels. It has been shown to improve on the GMM estimator in the first differenced model in terms of bias and root mean squared error. However, we show in this paper that in the covariance stationary panel data AR(1) model the expected values of the concentration parameters in the differenced and levels equations for the crosssection at time t are the same when the variances of the individual heterogeneity and idiosyncratic errors are the same. This indicates a weak instrument problem also for the equation in levels. We show that the 2SLS biases relative to that of the OLS biases are then similar for the equations in differences and levels, as are the size distortions of the Wald tests. These results are shown in a Monte Carlo study to extend to the panel data system GMM estimator.
Keywords: C12; C13; C23; 330; Dynamic Panel Data; System GMM; Weak Instruments; Panel; Momentenmethode; Schätztheorie